A Pilot Standardized Simulation-Based Mechanical Ventilation Curriculum Targeting Pulmonary and Critical Care Medicine and Critical Care Medicine Fellows - Amina Pervaiz; Asil Daoud; Abdulrazak Alchakaki; Shyam Ganti; Divya Venkat; Sarah Lee; Abdulghani Sankari (Avicenna Journal of Medicine, 2023)
Introduction The mastery of mechanical ventilation (MV) management is challenging, as it requires the integration of physiological and technological knowledge with critical thinking. Our aim was to create a standardized curriculum with assessment tools based on evidence-based practices to identify the skill deficit and improve knowledge in MV management.